A non-noble metal-based bifunctional catalyst, a preparation method and application thereof
Patent Information
- Application Number
- CN202311694379.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-11
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-12-11
AI Technical Summary
Non-precious metal-based catalysts suffer from low dispersion and easy sintering in the field of catalysis, resulting in a decrease in catalytic ability and making it difficult to replace precious metals in industrial applications.
A non-precious metal-based bifunctional catalyst was constructed in one step using a recrystallization hydrothermal synthesis strategy. By introducing active components such as Fe, Co, and Ni in situ onto the hydrogen-form ZSM-48 molecular sieve, the simultaneous construction of metal sites and acid sites was achieved, thereby improving metal dispersion and anti-sintering ability.
The prepared catalyst exhibits high metal dispersion and strong anti-sintering ability, demonstrating excellent catalytic activity and target product yield, especially in the isomerization reaction of chain alkane, where it shows good stability and efficiency.
Smart Images

Figure CN120132900B_ABST
Abstract
Description
Technical Field
[0001] This application relates to a non-precious metal-based bifunctional catalyst, its preparation method, and its application, belonging to the field of catalytic chemistry technology. Background Technology
[0002] Bifunctional catalytic materials, using molecular sieves as supports and incorporating multiple metal species, have been applied in various catalytic fields, particularly in cascade reactions requiring different catalytic active sites, such as the hydrodeoxygenation of biomass platform molecules, CO2 hydrocarbon production, and the hydroisomerization of wax oils. The "metal-acidity" balance in bifunctional catalysts is crucial for constructing excellent alkane isomerization catalysts. Their metal components include both noble metals (Pt, Pd, Ru, etc.) and non-noble metals (Ni, Co, Mo, etc.). Noble metals Pt and Pd have been widely used industrially due to their excellent dehydrogenation / hydrogenation performance, but their scarcity has led to supply shortages and high costs. Therefore, the development of non-noble metal-based bifunctional catalysts has attracted considerable attention. However, since the dehydrogenation / hydrogenation performance of non-noble metals is far inferior to that of noble metals, a much higher loading is required to achieve a balance between the acid and metal centers. The weak polarization ability of non-precious metals results in a weaker interaction between them and the support, making them prone to metal sintering at higher loading levels, leading to a decrease in catalytic activity [C.Dai, K.Du, C.Song, X.Guo, 2020, 6791-133.]. Therefore, designing and developing a catalyst preparation route with highly dispersed metals and good anti-sintering ability is key to promoting the industrial application of non-precious metal-based catalysts.
[0003] To address the shortcomings of non-precious metal-based catalysts, such as poor dispersion and easy sintering, numerous modification methods have been developed. These include metal doping (CN116590053A) and increasing the surface area of the support (CN103787368A). Introducing metals in situ during zeolite crystallization, utilizing the confinement effect of zeolite micropores or intergranular (intragranular) mesopores, is an effective means to improve metal dispersion and anti-sintering properties. Exploring simple and economical in-situ synthesis strategies is an extremely important research topic. Summary of the Invention
[0004] The purpose of this application is to develop a non-noble metal-based bifunctional catalytic material. This method achieves the simultaneous construction of metal and acid sites in the bifunctional catalyst through one-step recrystallization, resulting in a simple preparation process. Furthermore, the obtained non-noble metal-based bifunctional catalyst exhibits high metal dispersion and strong resistance to sintering.
[0005] One aspect of this application provides a non-precious metal-based bifunctional catalyst, the non-precious metal-based bifunctional catalyst comprising a support and an active component;
[0006] The support is hydrogen-form ZSM-48 molecular sieve;
[0007] The active components include active elements;
[0008] The active element is selected from at least one of Fe, Co, and Ni;
[0009] The dispersion of the active component is 5.5% to 40%.
[0010] Optionally, the dispersibility of the active component is independently selected from any value of 5.5%, 10%, 15%, 19%, 25%, 27%, 30%, 31%, 35%, 40%, or a range between any two of the above.
[0011] Optionally, the catalyst has an ellipsoidal crystal structure or a rod-like crystal bundle.
[0012] Optionally, the particle size of the active component is 2 nm to 20 nm.
[0013] Optionally, the particle size of the active component is independently selected from any value of 2nm, 2.5nm, 3nm, 5nm, 10nm, 15nm, 20nm or a range between any two of the above.
[0014] Optionally, the active component in the non-precious metal-based bifunctional catalyst has a mass content of 1 to 10 wt%, wherein the mass of the active component is based on the mass of the active element.
[0015] Optionally, the mass content of the active component in the non-precious metal-based bifunctional catalyst is independently selected from any value of 1 wt%, 2 wt%, 3 wt%, 3.48 wt%, 4.99 wt%, 5.03 wt%, 6 wt%, 7.28 wt%, 8 wt%, 9 wt%, 10 wt%, or a range between any two of the above.
[0016] Optionally, the ZSM-48 molecular sieve has a silicon-to-aluminum ratio (SiO2 to Al2O3 molar ratio) ≥30, or the ZSM-48 molecular sieve is a pure silicon molecular sieve.
[0017] Optionally, the non-noble metal-based bifunctional catalyst comprises a hydrogen-form ZSM-48 molecular sieve and metal species (Fe, Co, Ni). The non-noble metal-based bifunctional catalyst is constructed in one step using a recrystallization hydrothermal synthesis strategy, which involves the formation of the required acidic and metallic sites for the bifunctional catalyst. The ZSM-48 molecular sieve has a silica-to-alumina ratio (SiO2 to Al2O3 molar ratio) of 30 to ∞.
[0018] The mass content of metal species in the non-noble metal-based bifunctional catalyst is 1–10 wt%.
[0019] The metal species loading is calculated based on the atomic weight of the metal precursor.
[0020] The metal species mentioned are selected from at least one of nickel nitrate, nickel chloride, cobalt nitrate, cobalt chloride, ferric nitrate, ferric chloride, and ferric sulfate.
[0021] Another aspect of this application provides a method for preparing the above-mentioned non-precious metal-based bifunctional catalyst, which solves the above-mentioned technical problems by using suitable raw materials, finely adjusting the composition of the raw materials, and using a recrystallization hydrothermal crystallization method.
[0022] The preparation method includes:
[0023] After mixing the ZSM-48 molecular sieve matrix with the mother liquor, the mixture undergoes aging II and hydrothermal crystallization II to obtain bifunctional catalyst raw powder. After calcination and ion exchange, the non-precious metal-based bifunctional catalyst is obtained.
[0024] The mother liquor includes aluminum source II, template agent II, inorganic alkali II, metal precursor and water II.
[0025] Optionally, the ZSM-48 molecular sieve matrix is a silica-alumina or all-silica ZSM-48 molecular sieve.
[0026] Optionally, the preparation method of the ZSM-48 molecular sieve matrix includes:
[0027] The raw materials containing silicon source I, inorganic base I, and template agent I are mixed with water I, and then aged I, hydrothermal crystallization I, washed, dried, and calcined to obtain the ZSM-48 molecular sieve matrix.
[0028] Optionally, the silicon source I is selected from at least one of silica, silica sol, tetraethyl orthosilicate, and water glass;
[0029] The inorganic base I is selected from at least one of sodium hydroxide, sodium carbonate, potassium hydroxide, lithium hydroxide, and ammonia water;
[0030] The concentration of the ammonia solution is 25 wt%.
[0031] The template agent I is selected from at least one of hexamethylammonium bromide, hexamethylammonium chloride, hexamethylammonium hydroxide, and 1,6-hexamethylenediamine.
[0032] Optionally, the molar ratio of the inorganic base I to the silicon source I is 0.02 to 0.6;
[0033] The molar ratio of the template agent I to the silicon source I is 0.02 to 0.5;
[0034] The molar ratio of water I to silicon source I is 15 to 60;
[0035] The molar amount of silicon source I is calculated based on the molar amount of SiO2 in the selected silicon source I.
[0036] The molar amount of template agent I is calculated based on the molar amount of hexamethylammonium ions or 1,6-hexamethylenediamine in template agent I.
[0037] The molar amount of inorganic base I is calculated based on the hydroxide ions in inorganic base I.
[0038] Optionally, the molar ratio of the inorganic base I to the silicon source I is independently selected from any value of 0.02, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6 or a range between any two of the above.
[0039] Optionally, the molar ratio of the template agent I to the silicon source I is independently selected from any value of 0.02, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5 or a range between any two of the above.
[0040] Optionally, the molar ratio of water I to silicon source I is independently selected from any value of 15, 30, 45, 60 or a range between any two of the above.
[0041] Optionally, the raw material further contains aluminum source I; the aluminum source I is selected from at least one of aluminum nitrate, aluminum sulfate, sodium aluminate, boehmite, and aluminum chloride.
[0042] The molar ratio of silicon source I to aluminum source I is ≥50;
[0043] The molar amount of aluminum source I is calculated based on the molar amount of Al2O3 in aluminum source I.
[0044] Optionally, the aging temperature I is 25–80°C;
[0045] The aging time for the first stage is 2 to 8 hours.
[0046] Optionally, the aging temperature I is independently selected from any value of 25°C, 30°C, 40°C, 45°C, 50°C, 60°C, 70°C, 80°C, or a range between any two of the above.
[0047] Optionally, the aging time I is independently selected from any value of 2h, 4h, 6h, 8h or a range between any two of the above.
[0048] Optionally, the hydrothermal crystallization I is dynamic crystallization;
[0049] The temperature for hydrothermal crystallization I is 140–200°C;
[0050] The hydrothermal crystallization time is 48–120 h.
[0051] Optionally, the temperature of the hydrothermal crystallization I is independently selected from any value of 140°C, 160°C, 170°C, 200°C, or a range between any two of the above.
[0052] Optionally, the hydrothermal crystallization I time is independently selected from any value of 48h, 64h, 72h, 100h, 120h or a range between any two of the above.
[0053] Optionally, the dynamic crystallization I refers to being carried out in a batch reactor in a rotary oven, with the rotary oven rotating at a speed of 10–80 r / min.
[0054] After crystallization, the template agent is removed by filtration, washing, and calcination at 500℃ for 6 hours, thus obtaining the molecular sieve matrix.
[0055] Optionally, the mass ratio of the mother liquor to the ZSM-48 molecular sieve matrix is 5 to 70.
[0056] Optionally, the mass ratio of the mother liquor to the ZSM-48 molecular sieve mother liquor is independently selected from any value of 5, 10, 20, 30, 40, 50, 60, 70 or a range between any two of the above.
[0057] Optionally, aluminum source II is selected from at least one of aluminum nitrate, aluminum sulfate, sodium aluminate, boehmite, or aluminum chloride.
[0058] Optionally, the inorganic base II is selected from at least one of sodium hydroxide, potassium hydroxide, and lithium hydroxide.
[0059] Optionally, the template agent II is selected from at least one of hexamethyldiammonium bromide, hexamethyldiammonium chloride, and hexamethyldiammonium hydroxide.
[0060] Optionally, the metal precursor is selected from at least one of nickel nitrate, nickel chloride, cobalt nitrate, cobalt chloride, ferric nitrate, ferric chloride, and ferric sulfate.
[0061] Optionally, in the mother liquor, the concentration of aluminum source II is 0.001–0.1 mol / L, calculated as the concentration of Al ions;
[0062] In the mother liquor, the concentration of template agent II is 0.06–0.45 mol / L;
[0063] In the mother liquor, the concentration of inorganic base II is 0.1–0.8 mol / L, with OH... - Concentration meter.
[0064] Optionally, the concentration of the aluminum source II is independently selected from any value among 0.001 mol / L, 0.0019 mol / L, 0.0025, 0.055 mol / L, 0.085 mol / L, 0.1 mol / L, or a range between any two of the above.
[0065] Optionally, the concentration of the template agent II is independently selected from any value among 0.06 mol / L, 0.1 mol / L, 0.15 mol / L, 0.25 mol / L, 0.45 mol / L, or a range between any two of the above.
[0066] Optionally, the concentration of the inorganic base II is independently selected from any value among 0.1 mol / L, 0.2 mol / L, 0.25 mol / L, 0.3 mol / L, 0.4 mol / L, 0.52 mol / L, 0.6 mol / L, 0.7 mol / L, and 0.8 mol / L, or a range between any two of the above.
[0067] Optionally, the amount of the metal precursor added is 1 wt% to 15 wt% of the ZSM-48 molecular sieve matrix, calculated based on the metal content in the metal precursor.
[0068] Optionally, the amount of the metal precursor added is independently selected from any value of 1 wt%, 3 wt%, 4 wt%, 5 wt%, 8 wt%, 9 wt%, 10 wt%, 12 wt%, 15 wt%, or a range between any two of the above.
[0069] Optionally, the aging temperature II is 30–80°C;
[0070] The aging time for the second stage is 2 to 8 hours.
[0071] Optionally, the aging temperature II is independently selected from any value of 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, or a range between any two of the above.
[0072] Optionally, the aging time II is independently selected from any value of 2h, 3h, 4h, 5h, 6h, 7h, 8h or a range between any two of the above.
[0073] Optionally, the temperature of the hydrothermal crystallization II is 120–200°C; and the time of the hydrothermal crystallization II is 48–120 h.
[0074] Optionally, the temperature of the hydrothermal crystallization II is independently selected from any value of 120°C, 140°C, 160°C, 180°C, 200°C, or a range between any two of the above.
[0075] Optionally, the time for hydrothermal crystallization II is independently selected from any value of 48h, 60h, 72h, 84h, 96h, 108h, 120h or a range between any two of the above.
[0076] Optionally, the hydrothermal crystallization II is dynamic crystallization under autogenous pressure;
[0077] The dynamic crystallization refers to being carried out in a batch reactor within a rotary oven;
[0078] The rotational speed of the rotary oven is 10-80 r / min.
[0079] Optionally, the calcination temperature is 400–600°C;
[0080] The roasting time is 1 to 8 hours.
[0081] Optionally, the roasting temperature is independently selected from any value of 400°C, 450°C, 500°C, 520°C, 550°C, 600°C, or a range between any two of the above.
[0082] Optionally, the roasting time is independently selected from any value of 1h, 2h, 4h, 6h, 8h or a range between any two of the above.
[0083] Optionally, the obtained catalyst powder is calcined at 550°C in air for 6 hours to remove the template agent, and then subjected to ion exchange to obtain the bifunctional catalyst.
[0084] Another aspect of this application provides the application of the above-mentioned non-noble metal-based bifunctional catalyst in the catalytic isomerization reaction of chain alkane, the application including:
[0085] Under hydrogen I conditions, a feedstock containing chain alkanes comes into contact with a pretreated non-precious metal-based bifunctional catalyst and undergoes an isomerization reaction.
[0086] The chain alkane is selected from C6 to C6. 18 At least one of the n-chain alkanes.
[0087] Optionally, the pretreatment conditions are as follows: the non-noble metal-based bifunctional catalyst is reduced and activated under a hydrogen II atmosphere;
[0088] The reduction and activation temperature is 450–600℃, and the reduction and activation time is 1–5 hours.
[0089] Optionally, the reduction and activation temperature is independently selected from any value of 450°C, 500°C, 550°C, 600°C, or a range between any two of the above.
[0090] Optionally, the reduction and activation time is independently selected from any value of 1h, 2h, 3h, 4h, 5h or a range between any two of the above.
[0091] Optionally, the isomerization reaction is carried out at a temperature of 200–370°C;
[0092] The pressure of the isomerization reaction is 0–4 MPa;
[0093] The mass hourly space velocity (MSV) of hydrogen I is 0.5–10 h⁻¹. -1 ;
[0094] In the isomerization reaction, the volume ratio of hydrogen I to the chain alkane is 10 to 400.
[0095] Optionally, the temperature of the isomerization reaction is independently selected from any value of 200°C, 250°C, 290°C, 300°C, 305°C, 350°C, 370°C, or a range between any two of the above.
[0096] Optionally, the pressure of the isomerization reaction is independently selected from any value of 0 MPa, 1 MPa, 2 MPa, 3 MPa, 4 MPa, or a range between any two of the above.
[0097] Optionally, the mass hourly space velocity of the hydrogen I is independently selected from 0.5 h⁻¹. -1 1h -1 2h -1 4h -1 6h -1 8h -1 10h -1 Any value in or a range between any two of the above.
[0098] Optionally, the volume ratio of hydrogen I to the chain alkane is independently selected from any value of 10, 50, 100, 150, 200, 250, 300, 350, 400 or a range between any two of the above.
[0099] Optionally, as a specific implementation, the application includes: the above-mentioned non-precious metal-based catalyst is reduced and activated under an H2 atmosphere, and after activation, the temperature is lowered to the reaction temperature. Then, the raw material containing chain alkanes is contacted with the chain alkane isomerization catalyst for reaction.
[0100] The beneficial effects that this application can produce include:
[0101] (1) This application provides a method for synthesizing non-noble metal-based bifunctional catalysts in situ, which realizes the simultaneous construction of acid centers and metal centers of bifunctional catalysts in one step through a recrystallization strategy.
[0102] (2) The non-precious metal-based bifunctional catalyst prepared in this application has the advantages of high metal dispersion and strong anti-sintering ability.
[0103] (3) The method used in this application enables the one-step construction of metal sites and acid sites, and the process is simple and economical.
[0104] (4) The bifunctional catalyst prepared by this method has the advantages of high metal dispersion and good stability. It exhibits excellent catalytic activity and target product yield in the isomerization reaction of chain alkane. Attached Figure Description
[0105] Figure 1 X-ray diffraction (XRD) patterns of the bifunctional catalysts prepared in Examples 1-5
[0106] Figure 2 The image shows a scanning electron microscope (SEM) image of the bifunctional catalyst prepared in Example 1, with a scale bar of 1 μm.
[0107] Figure 3 The image shows a transmission electron microscope (TEM) image of the bifunctional catalyst prepared in Example 1, with a scale bar of 20 nm.
[0108] Figure 4 The image shows an SEM image of the bifunctional catalyst prepared in Example 3, with a scale bar of 2 μm. Detailed Implementation
[0109] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.
[0110] Unless otherwise specified, all raw materials used in the embodiments of this application were purchased through commercial channels.
[0111] The specific information of the various substances used in the examples is as follows:
[0112] Silica sol (Qingdao Marine Chemical Co., Ltd., 30wt% SiO2);
[0113] Silica (Maclean, 95wt% SiO2);
[0114] Tetraethyl orthosilicate (TEOS) (Comio, >98wt%);
[0115] Al2(SO4)3·18H2O (Sinopharm Group, 98wt%)
[0116] Al(NO3)3·9H2O (Sinopharm Group, 99wt%)
[0117] Boehmite (Maclean, 66 wt% Al2O3, 33 wt% H2O);
[0118] NaOH (Sinopharm Group, >96wt%)
[0119] KOH (Komeo, 85wt%);
[0120] HMBr (Aladdin, 98wt%)
[0121] HMCl (Aladdin, 98wt%)
[0122] n-Dodecane (Aladdin, 99.8 wt%)
[0123] High-purity hydrogen (Dalian Institute of Chemical Physics, 99.9 wt%)
[0124] Al2O3 (Sinopharm Group, analytical grade)
[0125] Deionized water (homemade).
[0126] In the embodiments of this application, the conversion rate and yield are calculated as follows:
[0127]
[0128]
[0129] In this embodiment, XRD testing was performed using a Bruker D8 Advance X-ray diffractometer, TEM testing was performed using a JEM-2100F instrument, and SEM testing was performed using a JSM-7800F instrument.
[0130] Preparation Example 1
[0131] Preparation of ZSM-48 molecular sieve precursor:
[0132] Under stirring conditions, 0.16 g Al2(SO4)3·18H2O, 1.01 g HMBr, and 0.78 g NaOH were dissolved in 37.29 g H2O. After complete dissolution, 18.26 g silica sol was added dropwise under stirring conditions. The initial gel was aged at 45 °C with stirring for 4 h, then transferred to a stainless steel reactor and placed in a rotary oven for hydrothermal crystallization at 170 °C and 60 r / min for 60 h. After crystallization, the mixture was rapidly cooled to room temperature with cold water, and after filtration, washing, drying, and calcination, the ZSM-48 molecular sieve matrix was obtained.
[0133] Following the above proportions and synthesis steps, the synthesis can be scaled up proportionally.
[0134] Preparation Example 2
[0135] Preparation of ZSM-48 molecular sieve precursor:
[0136] Under stirring conditions, 3.49 g HDA and 0.21 g NaOH were dissolved in 54 g H2O. After complete dissolution, 6.00 g fumed silica was added dropwise under stirring. The initial gel was aged at 40 °C with stirring for 4 h, then transferred to a stainless steel reactor and placed in a rotary oven for hydrothermal crystallization at 160 °C and 60 r / min for 72 h. After crystallization, the gel was rapidly cooled to room temperature with cold water, and then filtered, washed, dried, and calcined to obtain the ZSM-48 molecular sieve matrix.
[0137] Following the above proportions and synthesis steps, the synthesis can be scaled up proportionally.
[0138] Example 1
[0139] A mother liquor was prepared by dissolving 2.0 g NaOH, 0.25 g Al2(SO4)3·18H2O, 4.35 g HMBr, and 0.74 g Ni(NO3)2 in 120 g water. 6.00 g of the ZSM-48 molecular sieve obtained in Preparation Example 1 was added to the mother liquor. The mixture was aged at 30 °C with stirring for 3 h, then transferred to a 200 ml stainless steel reactor and placed in a rotary oven for hydrothermal crystallization at 160 °C and 60 r / min for 96 h. After crystallization, the mixture was rapidly cooled to room temperature with cold water, filtered, washed, and dried to obtain the sodium-type catalyst powder. The XRD pattern of this catalyst powder is shown below. Figure 1 As shown, this is a pure-phase ZSM-48 molecular sieve, and no diffraction peaks belonging to metallic Ni species were found. (From the SEM image...) Figure 2 As can be seen from the TEM image, the catalyst exhibits ellipsoidal crystals. Figure 3 As can be seen, metallic Ni is in a highly dispersed state with a diameter of approximately 2.5 nm. The dispersion of the metal particles in the catalyst was tested using CO pulsed chemisorption, and the dispersion of metallic Ni was found to be 30%.
[0140] The catalyst powder was calcined at 520°C in air for 4 hours and then ion-exchanged at 90°C for 3 hours using a 1 mol / L ammonium chloride solution to obtain the desired hydrogen-form catalyst. XRF analysis showed that its Ni loading was 4.99 wt%.
[0141] Example 2
[0142] A mother liquor was prepared by dissolving 2.0 g NaOH, 0.25 g Al2(SO4)3·18H2O, 4.35 g HMBr, and 0.52 g Ni(NO3)2 in 120 g of water. 6.00 g of the ZSM-48 molecular sieve obtained in Preparation Example 1 was added to the mother liquor. The mixture was aged at 30 °C with stirring for 3 h, then transferred to a 200 ml stainless steel reactor and placed in a rotary oven for hydrothermal crystallization at 160 °C and 60 r / min for 96 h. After crystallization, the mixture was rapidly cooled to room temperature with cold water, filtered, washed, and dried to obtain the sodium-type catalyst powder. The XRD pattern of this catalyst powder is shown below. Figure 1 As shown, this is a pure-phase ZSM-48 molecular sieve, and no diffraction peaks belonging to the metallic Ni species were found. The catalyst morphology is similar to that of the examples, with metallic Ni consisting of highly dispersed spherical particles with a diameter of approximately 2 nm. The dispersion of the metal particles in the catalyst was tested using CO pulsed chemisorption, and the dispersion of metallic Ni was found to be 35%.
[0143] The catalyst powder was calcined at 550°C in air for 2 hours and then ion-exchanged at 90°C for 3 hours using a 1 mol / L ammonium chloride solution to obtain the desired hydrogen-form catalyst. XRF analysis showed that its Ni loading was 3.48 wt%.
[0144] Example 3
[0145] A mother liquor was prepared by dissolving 1.2 g NaOH, 0.15 g Al2(SO4)3·18H2O, 4.35 g HMBr, and 0.74 g Ni(NO3)2 in 120 g water. 6.00 g of the ZSM-48 molecular sieve obtained in Preparation Example 2 was added to the mother liquor. The mixture was aged at 30 °C with stirring for 3 h, then transferred to a 200 ml stainless steel reactor and placed in a rotary oven for hydrothermal crystallization at 160 °C and 60 r / min for 96 h. After crystallization, the mixture was rapidly cooled to room temperature with cold water, filtered, washed, and dried to obtain the sodium-type catalyst powder. The XRD pattern of this catalyst powder is shown below. Figure 1 As shown, this is a pure-phase ZSM-48 molecular sieve, and no diffraction peaks belonging to metallic Ni species were found. (SEM image) Figure 4 The catalyst morphology shows a rod-like bundle of crystals, with highly dispersed spherical Ni particles approximately 5.0 nm in diameter. The dispersion of the metal particles in the catalyst was measured using pulsed CO chemisorption, yielding a Ni dispersion of 27%.
[0146] The catalyst powder was calcined at 500°C in air for 6 hours and then ion-exchanged at 90°C for 3 hours using a 1 mol / L ammonium chloride solution to obtain the desired hydrogen-form catalyst. XRF analysis showed that its Ni loading was 5.03 wt%.
[0147] Example 4
[0148] A mother liquor was prepared by dissolving 1.2 g NaOH, 0.15 g Al2(SO4)3·18H2O, 4.35 g HMBr, and 0.52 g Ni(NO3)2 in 120 g of water. 6.00 g of the ZSM-48 molecular sieve obtained in Preparation Example 2 was added to the mother liquor. The mixture was aged at 30 °C with stirring for 3 h, then transferred to a 200 ml stainless steel reactor and placed in a rotary oven for hydrothermal crystallization at 160 °C and 60 r / min for 96 h. After crystallization, the mixture was rapidly cooled to room temperature with cold water, filtered, washed, and dried to obtain the sodium-type catalyst powder. The XRD pattern of this catalyst powder is shown below. Figure 1 As shown, this is a pure-phase ZSM-48 molecular sieve, and no diffraction peaks belonging to the metallic Ni species were found. The catalyst morphology is similar to that of Example 3, with the metallic Ni consisting of highly dispersed spherical particles with a diameter of approximately 3.0 nm. The dispersion of the metal particles in the catalyst was tested using CO pulsed chemisorption, and the dispersion of metallic Ni was found to be 31%.
[0149] The catalyst powder was calcined at 500°C in air for 6 hours and then ion-exchanged at 90°C for 3 hours using a 1 mol / L ammonium chloride solution to obtain the desired hydrogen-form catalyst. XRF analysis showed that its Ni loading was 5.03 wt%.
[0150] Example 5
[0151] A mother liquor was prepared by dissolving 2.5g NaOH, 0.25g Al2(SO4)3·18H2O, 4.35g HMBr, and 1.04g Ni(NO3)2 in 120g water. 6.00g of the ZSM-48 molecular sieve obtained in Preparation Example 1 was added to the mother liquor. The mixture was aged at 30℃ with stirring for 3 hours, then transferred to a 200ml stainless steel reactor and placed in a rotary oven for hydrothermal crystallization at 160℃ and 60r / min for 96 hours. After crystallization, the mixture was rapidly cooled to room temperature with cold water, filtered, washed, and dried to obtain the sodium-type catalyst powder. The XRD pattern of this catalyst powder is shown below. Figure 1 As shown, this is a pure-phase ZSM-48 molecular sieve, and no diffraction peaks belonging to the metallic Ni species were found. The catalyst morphology is similar to that of Example 1, with the metallic Ni consisting of highly dispersed spherical particles with a diameter of approximately 3.0 nm. The dispersion of the metal particles in the catalyst was tested using CO pulsed chemisorption, and the dispersion of metallic Ni was found to be 19%.
[0152] The catalyst powder was calcined at 500°C in air for 6 hours and then ion-exchanged at 90°C for 3 hours using a 1 mol / L ammonium chloride solution to obtain the desired hydrogen-form catalyst. XRF analysis showed that its Ni loading was 7.28 wt%.
[0153] Catalytic performance verification:
[0154] The non-precious metal-based bifunctional catalysts obtained in Examples 1-5 were subjected to ion exchange and calcination to obtain hydrogen-form catalysts. These catalysts were then pressed into tablets and crushed into 20-40 mesh particles for later use.
[0155] The catalytic performance of the catalyst was evaluated using the hydroisomerization reaction of n-dodecane. The reactant was 99.8 wt% n-dodecane. Before the reaction, the catalyst was activated at 550 °C for 3 h under a hydrogen atmosphere at atmospheric pressure. After the temperature was lowered to the reaction temperature, the pressure was adjusted to 2.0 MPa, and then n-dodecane was introduced into the reaction system using a dual-plunger pump to initiate the reaction. The volume ratio of hydrogen to n-dodecane was maintained at 10 during the reaction.
[0156] The results are shown in Table 1.
[0157] Table 1 Catalytic performance of catalysts in Examples 1-5
[0158]
[0159] The above description is merely a few embodiments of this application and is not intended to limit this application in any way. Although this application discloses preferred embodiments as described above, it is not intended to limit this application. Any changes or modifications made by those skilled in the art without departing from the scope of the technical solution of this application using the disclosed technical content are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A non-precious metal-based bifunctional catalyst, characterized in that, The non-precious metal-based bifunctional catalyst includes a support and an active component; The support is hydrogen-form ZSM-48 molecular sieve; The active components include active elements; The active element is selected from at least one of Fe, Co, and Ni; The dispersion of the active component was tested using CO pulsed chemisorption. The dispersion of the active component is 5.5% to 40%; The active component in the non-precious metal-based bifunctional catalyst has a mass content of 2-10 wt%, wherein the mass of the active component is based on the mass of the active element. The particle size of the active component is 2 nm to 20 nm; The non-noble metal-based bifunctional catalyst is prepared by a method comprising the following steps: After mixing the ZSM-48 molecular sieve matrix with the mother liquor, the mixture undergoes aging II and hydrothermal crystallization II to obtain bifunctional catalyst raw powder. After calcination and ion exchange, the non-precious metal-based bifunctional catalyst is obtained. The mother liquor includes aluminum source II, template agent II, inorganic alkali II, metal precursor and water II.
2. The non-noble metal-based bifunctional catalyst according to claim 1, characterized in that, The catalyst has an ellipsoidal crystal structure or a rod-like crystal bundle.
3. The non-noble metal-based bifunctional catalyst according to claim 1, characterized in that, The ZSM-48 molecular sieve has a silicon-to-aluminum ratio (SiO2 to Al2O3 molar ratio) of not less than 30, or the ZSM-48 molecular sieve is a pure silicon molecular sieve.
4. A method for preparing a non-noble metal-based bifunctional catalyst according to any one of claims 1 to 3, characterized in that, The preparation method includes: After mixing ZSM-48 molecular sieve matrix with mother liquor, the mixture is aged in II and hydrothermally crystallized at 120~200℃ for 48~120h to obtain bifunctional catalyst raw powder. After calcination at 400~600℃ for 1~8h and ion exchange, the non-precious metal-based bifunctional catalyst is obtained. The mother liquor includes aluminum source II, template agent II, inorganic alkali II, metal precursor and water II; The mass ratio of the mother liquor to the ZSM-48 molecular sieve matrix is 5~70; In the mother liquor, the concentration of aluminum source II is 0.001~0.1 mol / L, calculated as Al ion concentration; the concentration of template agent II is 0.06~0.45 mol / L; and the concentration of inorganic base II is 0.1~0.8 mol / L, calculated as OH ion concentration. - Concentration meter; The amount of the metal precursor added is 1wt% to 15wt% of the ZSM-48 molecular sieve matrix, calculated based on the metal content in the metal precursor.
5. The preparation method according to claim 4, characterized in that, The preparation method of the ZSM-48 molecular sieve matrix includes: The raw material containing silicon source I, inorganic base I, and template agent I is mixed with water I and then aged I and hydrothermal crystallization I to obtain the ZSM-48 molecular sieve matrix. The silicon source I is selected from at least one of silica, silica sol, tetraethyl orthosilicate, and water glass; The inorganic base I is selected from at least one of sodium hydroxide, sodium carbonate, potassium hydroxide, lithium hydroxide, and ammonia water; The template agent I is selected from at least one of hexamethylammonium bromide, hexamethylammonium chloride, hexamethylammonium hydroxide, and 1,6-hexamethylenediamine; The molar ratio of the inorganic base I to the silicon source I is 0.02~0.6; The molar ratio of the template agent I to the silicon source I is 0.02~0.5; The molar ratio of water I to silicon source I is 15~60; The molar amount of silicon source I is calculated based on the molar amount of SiO2 in the selected silicon source I. The molar amount of template agent I is calculated based on the molar amount of hexamethylammonium ions or 1,6-hexamethylenediamine in template agent I. The molar amount of the inorganic base I is calculated based on the hydroxide ions in the inorganic base I. The raw material also contains aluminum source I; the aluminum source I is selected from at least one of aluminum nitrate, aluminum sulfate, sodium aluminate, boehmite, and aluminum chloride; The molar ratio of silicon source I to aluminum source I is ≥50; The molar amount of aluminum source I is calculated based on the molar amount of Al2O3 in aluminum source I.
6. The preparation method according to claim 5, characterized in that, The aging temperature for step I is 25~80℃; The aging time for the first stage is 2-8 hours; The hydrothermal crystallization I is dynamic crystallization; The temperature for hydrothermal crystallization I is 140~200°C; The hydrothermal crystallization time is 48~120h.
7. The preparation method according to claim 4, characterized in that, Aluminum source II is selected from at least one of aluminum nitrate, aluminum sulfate, sodium aluminate, boehmite, or aluminum chloride; The inorganic base II is selected from at least one of sodium hydroxide, potassium hydroxide, and lithium hydroxide; The template agent II is selected from at least one of hexamethyldiammonium bromide, hexamethyldiammonium chloride, and hexamethyldiammonium hydroxide; The metal precursor is selected from at least one of nickel nitrate, nickel chloride, cobalt nitrate, cobalt chloride, ferric nitrate, ferric chloride, and ferric sulfate.
8. The preparation method according to claim 4, characterized in that, The aging temperature for the second stage is 30~80℃; The aging time for the second stage is 2 to 8 hours.
9. The application of a non-noble metal-based bifunctional catalyst according to any one of claims 1 to 3 in the isomerization reaction of chain alkane, characterized in that, The applications include: Under hydrogen I conditions, a feedstock containing chain alkanes comes into contact with a pretreated non-precious metal-based bifunctional catalyst and undergoes an isomerization reaction. The chain alkane is selected from C6~C6. 18 At least one of the n-chain alkanes.
10. The application according to claim 9, characterized in that, The pretreatment conditions are as follows: the non-noble metal-based bifunctional catalyst is reduced and activated under a hydrogen II atmosphere; The reduction and activation temperature is 450~600℃, and the reduction and activation time is 1~5h; The isomerization reaction is carried out at a temperature of 200~370°C; The pressure of the isomerization reaction is 0~4MPa; The mass hourly space velocity (MSV) of hydrogen I is 0.5–10 h⁻¹. -1 ; In the isomerization reaction, the volume ratio of hydrogen I to the chain alkane is 10~400.
Citation Information
Patent Citations
Mesoporous ZSM-5 zeolite, mesoporous ZSM-5 zeolite-loaded metal sulfide catalyst and application
CN103787368A
Method and device for producing hydrogen by efficiently gasifying coal
CN116590053A
Long chain paraffin hydrogenation heterogeneous condensation freezing point depressing method and catalyst thereof
CN102942958A
ZSM-48 molecular sieve and preparation method thereof, low-carbon alkane isomerization catalyst and preparation method and application thereof
CN115108563A
ZSM-48 molecular sieve as well as preparation method and application thereof
CN116789149A
